PENGARUH PEMBERIAN MINYAK BIJI JINTEN HITAM TERHADAP KADAR INTERLEUKIN-6 PADA PEROKOK AKTIF SEHAT - Arif Santoso; Akrom Akrom; Laela Hayu Nuraini; Titiek Hidayati (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Exposure to cigarette smoke causes cellular oxidative stress and is the key to the inflammatory process in the lungs. Black cumin seed oil (MBJH) is one of the traditional medicines that is proven to contain the active substances timoquinone, nigelon and negelin which have antioxidant and immunomodulatory effects. Interleukin-6 (IL-6) is a proinflammatory cytokine and a multifunctional cytokine that is very important for determining the immune response, cell survival, apoptosis and proliferation and is a protumorogenic agent in many cancers. The purpose of this study was to determine the levels of IL-6 in healthy active smokers after being given MBJH at a dose of 0.5 ml/capsule. The research design used was a single blind Randomized Controlled Trial (RCT). A total of 39 healthy healthy active smokers were divided into 4 groups: Group 1 was given a placebo 3x1 capsules/day, group 2 was given MBJH 3x1 capsules/day, group 3 was given MBJH 3x2 capsules/day and group 4 was given MBJH 3x3 capsules/day. The placebo and MBJH interventions were administered for 30 days. Statistical analysis obtained showed that there was no significant difference in the mean levels of IL-6 between the treatment group and the placebo group with p>0.05. The results showed that the use of MBJH for 30 days can reduce the average level of Interleukin-6 but not significantly in healthy active smokers.